Short-term Effect of Garlic Extract on Patients with Dyslipidemia - Limbu, A; Rauniar, GP; Sharma, SK; Panday, DR; Shah, BK; Subedi, M (Nepal Medical College Journal, 2019)
Dyslipidemia is a metabolic abnormality leading to a persistent increase in the plasma concentration of cholesterol and triglycerides. Dyslipidemia is known to promote atherosclerosis. It is a complex disease and is a major risk factor for adverse cardiovascular events. Allium sativum commonly known as garlic has been found to have several medicinal value including, lipid-lowering property, blood pressure decreasing, anti-diabetic, anti-cancer and anti-oxidant activity. It was a double-blind, two-parallel-group, prospective interventional clinical trial. Total no of 112 patients were enrolled in the study and divided into two equal groups (56 in each group) viz; Group 1 (Lasuna TM) and Group 2 (placebo). Lipid profile was measured at day 0 and 90. Independent–sample‘t’ test was applied to find out the significant difference between the two groups, P-value being 0.05. The mean difference Total Serum Cholesterol, Serum Triglyceride, Serum LDL Cholesterol and Serum VLDL cholesterol on day 0 was nonsignificant with p being 0.539, 0.811, 0.230, 0.770 and 0.811 and on 90th day was significantly lower in group taking garlic with p being 0.001, 0.014, 0.003 and 0.008 respectively whereas Serum HDL cholesterol on 90th day was significantly higher in group taking garlic with p being 0.001. Garlic, when given as supplement decreases Total Serum Cholesterol, Serum Triglycerides, Serum LDL Cholesterol and Serum VLDL Cholesterol and on the other hand it increases Serum HDL Cholesterol.